NISAN ARCA SITUS MAKAM KUNO MANUBA KECAMATAN MALLUSETASI KABUPATEN BARRU - Mene, Bau (BALAI ARKEOLOGI PAPUA, 2011)
Statue tomb at the site of Manuba ancient grave at Mallusetasi District in Barru Residence. The problem of this research is the background and functions statue tomb using at the ancient grave surrounding. This researcrch uses qualitative research method. Tomb means sign, sometimes made of stone, wood and other material in various styles and forms. One of the form is statue. The using of statue tomb is for a symbol of the dead people and their social status.